2011
DOI: 10.5589/q11-011
|View full text |Cite
|
Sign up to set email alerts
|

A Parametric study and experimental testing of lunar-wheel suspension on dynamic terrainability

Abstract: The development of a flexible metallic wheel proved to be one of the most challenging and time-consuming aspects of the Lunar Roving Vehicle of the Apollo missions (V. Asnani, D. Delap, and C. Creager. 2009. Journal of Terramechanics, 46: 89 103). The design was realized through an iterative trial and error design process, driven primarily by manufacturability and physical testing. Although the wire-mesh-compliant wheel design was identified as the best choice for the Lunar Roving Vehicle, mission scenarios ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In this vehicle, no coil spring is present, and the suspension and tire stiffness may be combined into a joined stiffness k and sprung and unsprung mass can be condensed in a unique mass ms, as shown in Figure 10. This leads to a single-DOF system, as suggested in Faragalli et al (2011), whose model parameters are reported in Table 5.
Figure 10.General one degrees of freedom quarter-car model for the lunar rover vehicle.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this vehicle, no coil spring is present, and the suspension and tire stiffness may be combined into a joined stiffness k and sprung and unsprung mass can be condensed in a unique mass ms, as shown in Figure 10. This leads to a single-DOF system, as suggested in Faragalli et al (2011), whose model parameters are reported in Table 5.
Figure 10.General one degrees of freedom quarter-car model for the lunar rover vehicle.
…”
Section: Resultsmentioning
confidence: 99%
“…In this vehicle, no coil spring is present and the suspension and tire stiffness may be combined into a joined stiffness k, as well as, sprung and unsprung mass can be condensed in a unique mass m s , as shown in Figure 10. This leads to a single degree of freedom system, as suggested in Faragalli et al (2011), whose model parameters are reported in Table 5. The state and measurement vector of the corresponding estimation problem reduce respectively to x = [y 1 − hẏ 1 k tot ] T and z = [ÿ 1 ], whereas the transition matrix A can be obtained from that of the 2 DOF QC case by removing the third and fourth line and column, and matrices B, C, G can be adapted accordingly.…”
Section: Application To Planetary Roving Vehiclesmentioning
confidence: 99%
“…Nevertheless, a substantial amount of NPTs that has been proposed is composed of a single elastomeric material such as TPU. 33,[124][125][126] Other approaches are based on alloys such as steel 102 or a shape memory alloy, 11 as of the examples proposed by NASA. Furthermore, tire sections can have distinct material compositions and production techniques.…”
Section: Applications Materials and Production Techniquesmentioning
confidence: 99%
“…This example dates to 2019 and is an evolution of the lunar roving vehicle tires, made of knitted metallic meshes, that were used during the Apollo (15/16/17) missions. [11][12][13][14][15] Some airless wheel concepts are already present in commercially available solutions for trailers, wheelchairs, or small electric scooters, with most of these being made from rubber or polymers. [16][17][18] Figure 1(g) shows an example of an electric scooter solid rubber tire.…”
Section: Introductionmentioning
confidence: 99%